Problems of computerization in the brunch of preschool education - Podolyaka А.Е (Kharkov National Pedagogical University, 2010)
The use of computer technologies was probed in preschool education. 27 pedagogical workers of child's preschool establishments took part in research. The differentiated approach is rotined in the selection of facilities of physical education of children of preschool age. The basic requirements are selected to the computer programs. Found out disparity between enhanceable demand on the computer programs and their introduction in an educational educate process. Multilevel classification and sequence is set in the selection of mobile games.